First‐hand sensory experience plays a limited role in children's early understanding of seeing and hearing as sources of knowledge: Evidence from typically hearing and deaf children. (20th August 2014) - Schmidt, Ellyn; Pyers, Jennie
<x xml:space="preserve">Abstract</x> One early‐developing component of theory of mind is an understanding of the link between sensory perception and knowledge formation. We know little about the extent to which children's first‐hand sensory experiences drive the development of this understanding, as most tasks capturing this early understanding target vision, with less attention paid to the other senses. In this study, 64 typically hearing children (Mage = 4.0 years) and 21 orally educated deaf children (Mage = 5.44 years) were asked to identify which of two informants knew the identity of a toy animal when each had differing perceptual access to the animal. In the 'seeing' condition, one informant saw the animal and the other did not; in the 'hearing' condition, one informant heard the animal and the other did not. For both hearing and deaf children, there was no difference between performance on hearing and seeing trials, but deaf children were delayed in both conditions. Further, within both the hearing and deaf groups, older children outperformed younger children on these tasks, indicating that there is a developmental progression. Taken together, the pattern of results suggests that experiences other than first‐hand sensory experiences drive children's developing understanding that sensory perception is associated with knowledge.